Natural convection with evaporation in a vertical cylindricalcavity under the effect of temperature-dependent surfacetension; Continuum Mechanics and Thermodynamics; Vol. 30, iss. 1 - Kozhevnikov D. А. Danil (2018, 2018)
Title screen